2014
DOI: 10.1371/journal.pmed.1001727
|View full text |Cite
|
Sign up to set email alerts
|

Equity-Oriented Monitoring in the Context of Universal Health Coverage

Abstract: As part of the Universal Health Coverage Collection, Ahmad Reza Hosseinpoor and colleagues discuss methodological considerations for equity-oriented monitoring of universal health coverage, and propose recommendations for monitoring and target setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
106
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 106 publications
(111 citation statements)
references
References 13 publications
3
106
0
2
Order By: Relevance
“…Another key success factor in the process in Indonesia was the concurrent development of specific software and technology for health inequality monitoring which enabled the use of local datasets. The existence of a technical handbook and easily accessible tools helped facilitate the application of the software to monitor health inequalities [79,11, 17]. At the heart of the collaborative process in Indonesia was the strong and ongoing support by the WHO country office, both at senior levels and by way of commitment and dedicated time of WHO staff, which helped maintain the momentum and relationships between stakeholders.…”
Section: Discussionmentioning
confidence: 99%
“…Another key success factor in the process in Indonesia was the concurrent development of specific software and technology for health inequality monitoring which enabled the use of local datasets. The existence of a technical handbook and easily accessible tools helped facilitate the application of the software to monitor health inequalities [79,11, 17]. At the heart of the collaborative process in Indonesia was the strong and ongoing support by the WHO country office, both at senior levels and by way of commitment and dedicated time of WHO staff, which helped maintain the momentum and relationships between stakeholders.…”
Section: Discussionmentioning
confidence: 99%
“…The health-related goal (SDG 3) calls upon countries to ‘ensure healthy lives and promote well-being for all at all ages’, with universal health coverage as the target that underpins all other health and health-related targets (SDG target 3.8) [5]. Health inequality monitoring is vital for tracking progress towards universal health coverage to ensure that disadvantaged populations achieve accelerated gains alongside overall improvement in the broader population, thus narrowing coverage gaps [6,7]. It is also important for countries to track progress towards national goals or global goals (if considered relevant in the national context).…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, measures to prevent catastrophic health expenditure and provision of quality care are of great concern to all countries, institutions, and the academia (1). High OOP payment was a major challenge to the people of Iran and many Iranians were unable to afford the cost in seeking for health care due to it (10). Previous studies in Iran have shown that the incidence of catastrophic health expenditures (CHE) ranges from 6% -17.7% at the national level (11,12), and 14.2% -22.2 % at the regional level (13,14), with an OOP payment of about 52.1% (15).…”
Section: Introductionmentioning
confidence: 99%